2014
DOI: 10.1016/j.rmed.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to multicase hypersensitivity pneumonitis is associated with the TNF-238 GG genotype of the promoter region and HLA-DRB1*04 bearing HLA haplotypes

Abstract: Hypersensitivity Pneumonitis (HP) is a lung inflammatory disorder caused by inhalation of organic particles by a susceptible host. Since only a small proportion of individuals exposed to HP-related antigens develop the disease, a genetic predisposition is largely suspected. However, studies regarding genetic susceptibility in this disease are scanty. We have previously found evidence supporting increased risk associated to the major histocompatibility complex (MHC) in sporadic HP. In the present study, we cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…In multivariable analysis, we found that Caucasian subjects were 9.33 times more likely to die or undergo a lung transplant during follow-up than non-Caucasian patients. These findings may support a genetic role as has been suggested in prior studies by others, in the pathogenesis or disease course of HP but require validation (21, 22) .…”
Section: Discussionsupporting
confidence: 80%
“…In multivariable analysis, we found that Caucasian subjects were 9.33 times more likely to die or undergo a lung transplant during follow-up than non-Caucasian patients. These findings may support a genetic role as has been suggested in prior studies by others, in the pathogenesis or disease course of HP but require validation (21, 22) .…”
Section: Discussionsupporting
confidence: 80%
“…[1][2][3] Pigeon-antigen-specific proliferative T cell responses are not associated with disease status 4 despite genetic association of HLA-DR with PFL suggesting CD4 + T cell involvement. 5 Detailed analysis of reactive T cell phenotypes in PFL is limited, whilst T reg appear reduced in PFL. 6 A role of lung microbial infections in exacerbating PFL and other lung conditions is suggested.…”
Section: Antibody and T Cell Responses Against Avian And Microbial Anmentioning
confidence: 99%
“…Gut microbial dysbiosis in the first year of life was associated with asthma in multiple birth cohort studies. [1][2][3][4][5] Microbial metabolites might play a crucial role in maintaining an adequate immune balance and preventing asthma through its influence on regulatory T-cells (Tregs) and the Foxp3 gene. 1,6 However, most data are derived from animal studies, whereas most human studies have focused on the association between infant gut microbiota and asthma-like symptoms at an age when a reliable diagnosis of asthma cannot yet be made.…”
Section: Gut Microbiota In Wheezing Preschool Children and The Associmentioning
confidence: 99%
“…Hypersensitivity pneumonitis (HP) is an interstitial lung disease resulting from complex interactions between antigen exposures and alleles of many genes 14 . HP development depends on the type, intensity, and duration of exposure to the inciting agent, host susceptibility, the site of interaction within the respiratory system, and the resulting level of dysregulation of the cellular and humoral immune response over time 5 . In the United States there is a significant increasing trend in overall age-adjusted mortality for HP 6 , with HP mortality in farm workers 10-50% more than expected 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Only a small proportion of exposed individuals develop HP indicating there are likely to be genetic factors involved in the development of the disease. It has been found by previous researchers that genes of the major histocompatibility complex (MHC) and the tumor necrosis factor alpha (TNF-α) were associated with HP 4,5,8 . The expression of MHC class II molecules is required for activation of T lymphocytes cells during immune response triggering.…”
Section: Introductionmentioning
confidence: 99%